ANALISIS YURIDIS TERHADAP MOGOK KERJA SEBAGAI ALASAN PEMUTUSAN HUBUNGAN KERJA (STUDI KASUS: PUTUSAN NOMOR 67 PK/PDT.SUS-PHI/2018) - Naomi Artha Nauli Arman; Andari Yurikosari (Jurnal Hukum Adigama, 2019)
A strike is a basic or normative right attached to workers so it needs to be protected. The meaning of strike is regulated in Law Number 13/2003 concerning Manpower Article 1 Paragraph (23), illegal strike is regulated in Decree of the Minister of Manpower and Transmigration Number KEPMEN-232/200. Regarding the Legal Effects of a Strike Invalid. Lately there have been cases of employers terminating employment with workers who are on strike. The main problem here is how the judicial analysis of the judge's decision on termination of employment by reason of a legal strike and how legal protection for workers who are terminated due to strikes at PT. Sanfu Indonesia. Conducting research methods in a normative, prescriptive manner, conducting research using primary and secondary data in the form of interviews and in the form of books or literature. With the conclusion, in accordance with the provisions of Law Number 13/2003 Concerning Labor Strikes conducted by workers is legal because workers have carried out strike procedures that are not in conflict with KEPMEN Number 232/2003 Concerning the Legal Results of Non-Strikes Legitimate. In terms of protection, the worker / laborer has received protection because the worker has obtained his right in the form of severance pay, and also because the worker is carrying out a legal strike, so that it is protected by Law No. 13 of 2003 concerning Labor Article 153.